Business Dispute Settlement Employment Chartering Agreement In The Perspective Of Legal Certainty - Saputra, Iqbal; Kusbianto, Kusbianto; Sitompul, Ariman (Legalpreneur Journal, 2024)
The background of the problems in this thesis research is a business dispute agreement chartering Pekerajaan with a peace decision between Antony Simon melaawan LAI MEE YEK that can be resolved through the mediation process. In conducting the mediation process in court with a peace decision (deed of Vandading) in the Medan District Court in accordance with the mediation implementation procedure as stipulated in PERMA No. 1 of 2016. The problems discussed in writing this thesis is how the legal regulations in the settlement of business disputes on the tort of default, how the settlement of cases of tort of default with the occurrence of peace (Dading) by the Medan District Court and how the settlement of business disputes chartering Pekeraja agreement with the Peace decision (deed Vandading) in Medan District Court. The research method used in the writing of this thesis is a type of normative-empirical legal research, by conducting doctoral research directly and using data collection tools in the form of interviews. Based on the results of research, the process of resolving default business disputes through a simple lawsuit based on perma number 4 of 2019 with a material lawsuit of at most Rp.500.000.000, - (five hundred million rupiah) in order to achieve legal certainty should be in the lawsuit the plaintiff appealed to the Chairman/panel of judges who examined and tried this case to put a temporary bail seizure (conservatoir beslagh) against the defendant's property both movable and immovable. In order to avoid greater financing and longer time in resolving this matter.